(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
Previous and current concrete is defined as concrete that contains little to no fine aggregate, coarse aggregate, or cement particles. It is considered "green binding" and is used in structural applications. Pervious concrete is also known as no-fine aggregate. Compared to ordinary concrete, it uses fewer raw materials. When utilised in pavement applications, pervious concrete aids in groundwater recharging, water direct drainage, and also has greater insulating qualities when used in walls. Current or previous building uses concrete that has been specially formulated to have a higher water permeability, allowing water to move through the structure’s interconnected huge pores. The findings of an investigation into the production of pervious concrete using low cement concentration and coarse aggregate are reported in this work.